2024
DOI: 10.3390/plants13030446
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Priming for Inducing Salinity Tolerance, Disease Resistance, Yield Attributes, and Alleviating Heavy Metal Toxicity in Plants

Jisun H. J. Lee,
Deepak M. Kasote

Abstract: In today’s time, agricultural productivity is severely affected by climate change and increasing pollution. Hence, several biotechnological approaches, including genetic and non-genetic strategies, have been developed and adapted to increase agricultural productivity. One of them is nano-priming, i.e., seed priming with nanomaterials. Thus far, nano-priming methods have been successfully used to mount desired physiological responses and productivity attributes in crops. In this review, the literature about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The potentially adverse effects of NPs on biogeochemical cycles, such as nitrogen turnover and carbon emissions, have also been discussed [ 90 ]. However, seed nanopriming minimizes the exposure of the environment to NPs and is thus less harmful than the foliar use of NPs [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentially adverse effects of NPs on biogeochemical cycles, such as nitrogen turnover and carbon emissions, have also been discussed [ 90 ]. However, seed nanopriming minimizes the exposure of the environment to NPs and is thus less harmful than the foliar use of NPs [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that NPs that are accumulated in plant roots tend to translocate to other tissues, such as newly developed seeds and plant shoots, and that NP translocation is significantly influenced by the properties of both plants and the characteristics of NPs [ 92 , 93 ]. In this regard, it is reported that the accumulation of Fe and Zn could be increased in wheat and maize grains due to nanopriming [ 91 , 94 , 95 ]. However, the chemical mechanisms behind the uptake, absorption, and transport of nanoparticles in plants remain unclear [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nano-priming of seeds has emerged as a novel and highly effective technique that favorably modifies the metabolism and signaling pathways of seeds [25], thereby impacting various stages of a plant's lifecycle, such as germination and overall plant growth [26]. Among the multitude of advantages associated with seed nano-priming, the most notable are improved plant growth and development [27], as well as increased nutritional value [28] and increased tolerance to stress [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ion transport should be regulated via the exclusion or storage of ions in vacuoles to maintain cellular homeostasis in the crucial parts of plant cells to minimize ionic toxicity [25]. In addition to these responses, the production of ROS and RNS is triggered [26]. The production of free radicals such as superoxide ions (O 2 − ), hydroxyl radicals (OH), singlet oxygen ( 1 O 2 ), and hydrogen peroxide (H 2 O 2 ) destroys metabolic activities during growth and development [27].…”
Section: Responses Of Cereal Plants To Saline Stressmentioning
confidence: 99%
“…When plant cells are exposed to low levels of salinity stress, signaling mechanisms, through specific proteins, the Ca 2+ transduction pathway, and ROS (at very low concentrations), induce gene expression [24,47]. Under salinity stress, mitochondria and chloroplasts work hard to improve the conditions of plants; however, as a side effect, the ROS levels increase rapidly because these sites are characterized by ROS production [3,26,38]. Osmotic stress and ion imbalance also lead to ROS production.…”
Section: Responses Of Cereal Plants To Saline Stressmentioning
confidence: 99%